2021
DOI: 10.1371/journal.pone.0250295
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic and clinicopathological significance of C-reactive protein/albumin ratio (CAR) in patients with gastric cancer: A meta-analysis

Abstract: Background In recent years, many studies have explored the potential prognostic utility of C-reactive protein/albumin ratio (CAR) in patients with gastric cancer (GC), however, the results remain conflicting. We thus performed a meta-analysis to determine the association of CAR and prognosis of GC. Methods This meta-analysis was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statement. PubMed, Web of science, Embase, and Cochrane Library were searched. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Many studies have investigated the prognostic value of the CRP/Alb ratio in a variety of cancer types (26,29,(32)(33)(34)(35). Yu et al showed that an elevated pretreatment CRP/Alb ratio was a prognostic marker of poor OS and CSS in patients with gastric cancer (26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many studies have investigated the prognostic value of the CRP/Alb ratio in a variety of cancer types (26,29,(32)(33)(34)(35). Yu et al showed that an elevated pretreatment CRP/Alb ratio was a prognostic marker of poor OS and CSS in patients with gastric cancer (26).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have investigated the prognostic value of the CRP/Alb ratio in a variety of cancer types (26,29,(32)(33)(34)(35). Yu et al showed that an elevated pretreatment CRP/Alb ratio was a prognostic marker of poor OS and CSS in patients with gastric cancer (26). A high CRP/Alb ratio was shown to be associated with clinicopathological features that reflect tumor progression in patients with gastric cancer (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C‐reactive protein (CRP), high sensitivity C‐reactive protein (hs‐CRP), tumor necrosis factor‐α (TNF‐α), soluble intercellular adhesion molecule (sICAM), and interleukin‐6 (IL‐6) are important inflammatory biomarkers in clinical trials (Farsi et al., 2019; Morvaridzadeh et al., 2020). The levels of TNF‐α (Htet et al., 2021), IL‐6 (Santos et al., 2021), and CRP (Yu et al., 2021) are closely related to the occurrence of gastric cancer. CRP is a classic acute phase protein and often elevated in serum during acute inflammation, gastric cancer, and other diseases (Hunter et al., 2021; Matsui et al., 2021).…”
Section: Introductionmentioning
confidence: 99%